The Role of Diffusion-Weighted MR Imaging in Detecting Malignant and Benign Pleural Thickening in Asbestos-Related Pleural Diseases - Koc, Mustafa; Poyraz, Ahmet Kursad (Erciyes Univ Sch Medicine, 2017)
Objective: The aim of this study was to evaluate the role of diffusion-weighted magnetic resonance imaging (dMRI) in differentiating between diffuse malignant and benign pleural thickening in asbestos-related pleural diseases. Materials and Methods: Sixty-two patients were included in the study. Thirty-two had a benign form and 30 had malignant pleural mesothelioma (MPM). The patient files and records belonging to those who underwent dMRI on a 1.5 T MR system between May 2014 and January 2016 in our clinic were examined retrospectively. The dMRI was performed with 0, 500, and 1000 mm(2)/s b-values. The apparent diffusion coefficient (ADC) map was generated, and means ADC values were determined from measurements of pleural thickening. Results: The mean ADC values were 1.94 +/- 0.09x10(-3) mm(2)/s and 0.84 +/- 0.05x10(-3) mm(2)/s in benign pleural disease and MPM, respectively. The mean ADC value in the malignant group was significantly lower than in the benign group (p< 0.05). Conclusion: Our results show that dMRI and ADC values are useful for differentiating between benign and malignant pleural thickening in asbestos-related pleural diseases. dMRI gives clues for the interpretation of whether pleural thickening is benign or malignant and can assist in the early detection of MPM.
Keywords: Diffusion-weighted imaging; ADC measurement; pleura; asbestosis; mesothelioma